ANALISIS ASPEK-ASPEK STUDI KELAYAKAN BISNIS PADA BAKERY HOME INDUSTRY COKOTABLE - Fadilla, Annisa Nurul; Rengganis Putri, Luh Ayu; Dewi, Novia Chintia; Oktaviani, Nabila Madarina; Hidhayatullah , Ryan; Halim Putra, Dimas Adi (Astha Grafika, 2025)
Abstract: This study aims to analyze the business feasibility of the home-based bakery enterprise